2018
DOI: 10.1177/1753944718786926
|View full text |Cite
|
Sign up to set email alerts
|

Results of 5-year follow-up study in patients with peripheral artery disease treated with PL-VEGF165 for intermittent claudication

Abstract: The therapeutic effect of angiogenesis induction by gene therapy persists for 5 years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 11 publications
0
19
0
3
Order By: Relevance
“…Intramuscular injection of a single dose of this drug, costing less than $50, delivers a plasmid DNA-carrying VEGF gene cloned under a CMV promoter and stimulates angiogenesis and blood supply to decrease the risk of amputation and death in patients suffering from PAD. A recent post-marketing surveillance study revealed a significant increase in pain-free walking distance by PAD patients and confirmed the therapeutic efficacy of this drug (56, 57). Recently, Spinraza® has become the first approved treatment for the rare and often fatal disease spinal muscular atrophy (SMA).…”
Section: Gene Therapy Drugs In the Marketmentioning
confidence: 63%
See 1 more Smart Citation
“…Intramuscular injection of a single dose of this drug, costing less than $50, delivers a plasmid DNA-carrying VEGF gene cloned under a CMV promoter and stimulates angiogenesis and blood supply to decrease the risk of amputation and death in patients suffering from PAD. A recent post-marketing surveillance study revealed a significant increase in pain-free walking distance by PAD patients and confirmed the therapeutic efficacy of this drug (56, 57). Recently, Spinraza® has become the first approved treatment for the rare and often fatal disease spinal muscular atrophy (SMA).…”
Section: Gene Therapy Drugs In the Marketmentioning
confidence: 63%
“…In situ delivery, or “in position” delivery, involves administration of the desired genetic material directly into the target cells or tissue. For example, Neovasculgen®, a plasmid vector carrying vascular endothelial growth factor (VEGF) gene, is directly injected into the target ischemic tissue to stimulate blood vessel growth (5557). This method is being explored to cure cystic fibrosis, muscular dystrophy, and cancer but still requires more technological advancement in delivery methods for a successful clinical outcome (5860).…”
Section: Somatic Cell Gene Therapymentioning
confidence: 99%
“…Some of the common side effects reported in patients receiving Zynteglo TM during the clinical trials were a low count of thrombocytes, numbness in hands and feet, pain in the bone, nausea, headache, and low blood calcium levels ( Deev et al, 2018 ).…”
Section: Safety and Efficacy Of Advanced Therapy Medicinal Products (mentioning
confidence: 99%
“…Considering the crucial role of VEGF-A in reparative osteogenesis, the osteoconductive potential of OCP, and our experience in gene-therapeutic drug development and clinical translation (Deev et al, 2018 ), we aimed to investigate and clinically translate a gene-activated bone substitute based on an OCP scaffold and VEGFA165 -carrying plasmid DNA (pDNA- VEGF ).…”
Section: Introductionmentioning
confidence: 99%